2005
DOI: 10.1080/00071660500064378
|View full text |Cite
|
Sign up to set email alerts
|

Age-related changes in the distribution of lean, fat with skin and bones in duck carcases

Abstract: The experimental birds were Pekin ducks (352 males and 352 females) reared to the age of 13 weeks. They were fed standard diets ad libitum. Starting from the second week, 21 males and 21 females were slaughtered every 7 d. Their carcases were divided into the following elements: neck, wings, legs, breast and back, which were then dissected into lean, skin with fat and bones. The body weights of one-day-old ducklings were similar (circa 62 g), but at 5 weeks of age the males were heavier than the females, and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
23
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 2 publications
5
23
1
Order By: Relevance
“…Also male ducklings consumed totally more food than females (P<0.05). This result is consistent with previous reports for body weight of male and female ducks [10][11][12] . Feed conversion ratio was only statistically significant (P<0.05) in the three weeks of rearing.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Also male ducklings consumed totally more food than females (P<0.05). This result is consistent with previous reports for body weight of male and female ducks [10][11][12] . Feed conversion ratio was only statistically significant (P<0.05) in the three weeks of rearing.…”
Section: Discussionsupporting
confidence: 83%
“…Slaughter age may be important in these parts. Bochno et al [11] reported that the deposition of fat and skin increased significantly up to 10 weeks of age (from 98 g in 2-week-old birds to 843 g in 10-weeks-old ones). However types of bell drinkers only affected the percentages of breast, wings and skin with subcutaneous fat.…”
Section: Tablo 2 Pekin öRdeklerinde Suluk Sistemi Ve Cinsiyetin Yem mentioning
confidence: 99%
See 1 more Smart Citation
“…There is not enough information about the effects of different housing systems, sex, and slaughter age on slaughter and carcass traits in native Turkish ducks. However, the best slaughter age for Pekin ducks has been accepted as 7 to 8 weeks (6). There is little research on the different housing systems for Pekin ducks in Turkey (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…In Pekin ducks after hatching, first growing part of the body is legs, which is followed by breast and wings. Leg muscles grow very quickly to the 2 wk of age and breast muscles to 7 wk of age (3,11). Maruyama et al (25) reported that breast muscle grows faster than whole body during the fattening period, so this study showed that development of breast in Pekin ducks was sensitive to rearing method.…”
Section: Discussionmentioning
confidence: 74%